A Training Based on Experiential Learning to Create the Entrepreneur-Characterized Youth - Eko Wanidison; Ihat Hatimah; Joni Rahmat Pramuda (Budapest International Research and Critics University, 2019)
A large number of entrepreneurs who grow in society can be an influencer of the progress of the economy of a nation. This is because the increase of entrepreneurs can lead poverty and unemployment to be minimized. To reach this stage, training is needed to improve the ability of the society to be more creative and innovative. This is as the objectives implemented in the Young Entrepreneur Academy (YEA) to create training programs that focus on creating entrepreneurs. The purpose of this study was to find out the success of YEA in creating prospective entrepreneurs. Furthermore, a descriptive qualitative approach was applied in this study, while, the data in this study were collected through interviews, observation, and documentation. The researchers found that the YEA has various planning programs with a vision to create prospective entrepreneurs who are adapted to the development of the business world. Thus, the YEA is more focused on carrying out training in practice than just a theory. The conclusion is the YEA makes the Experiential Learning program not to create prospective job seekers but aims at creating the candidates for opening jobs.